Visão computacional aplicada a manipulador robótico - Azevedo, Adriel Lima (2019)
With the objective of seeking improvements in industrial systems, obtaining interaction between automated equipment. This article presents some tools that give access to the development of programs for a computer vision system, aiming to detect obstacles in the robotic manipulator’s desktop, from a structured communication system, capable of capturing information and sending it to fast, processing and decision making, leading to the deviation of the manipulator’s trajectory. To this end, some theoretical topics on robotic manipulator, operation and movement methods, as well as Computer Vision’s tools using OpenCV for image processing and object recognition and ROS (Robotic Operating System) are discussed . Supports the diversity of tools to manipulate and detect a robot. The materials and methods used, which are the software and hardware necessary for the system implementation, are presented. At the end are described all the stages of development of the work, ending with the presentation of results and final comments.